Deleterious effects of neuronal accumulation of glycogen in flies and mice - Duran, Jordi (WILEY-VCH Verlag, 2012)
Under physiological conditions, most neurons keep glycogen synthase (GS) in an inactive form and do not show detectable levels of glycogen. Nevertheless, aberrant glycogen accumulation in neurons is a hallmark of patients suffering from Lafora disease or other polyglucosan disorders. Although these diseases are associated with mutations in genes involved in glycogen metabolism, the role of glycogen accumulation remains elusive. Here, we generated mouse and fly models expressing an active form of GS to force neuronal accumulation of glycogen. We present evidence that the progressive accumulation of glycogen in mouse and Drosophila neurons leads to neuronal loss, locomotion defects and reduced lifespan. Our results highlight glycogen accumulation in neurons as a direct cause of neurodegeneration.